Partisipasi Umat dalam Kemandirian Dana di Paroki Hati Kudus Yesus Laham - Godensius Daleq; Wilfridus Samdirgawijaya; Zakeus Daeng Lio (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2018)
The research showed that the forms of participation of the people is the power, property and the mind. The mechanism of participation is mandatory monthly donation program, the annual compulsory contributions, the garden parish, parish fields. The participation rate is power, tokenism and participation. The research of data analysis showed that the participation of the people cannot be measured using indicators of the level of participation, because any form of participation in the context of the independence of the funds related to each other. So the more suitable analytical framework for understanding the participation of the people is the idea of the circle of participation. Based on the idea of the circle of participation, then the model participation people in the independence of the fund in the parish of the Sacred Heart of Jesus Laham is participation cycle model. Cycle characterized by the benefits of participation, cooperation and partnership, mutual learning. Cycle participation in line with the core view of a church that looked at the relationship between participation intertwined with the alliance. Participation in the form of donations turned fellowship, and communion as participation turned container. So, they can say that participation is a tension between the alliance and donations.